THE MEANING OF WAGE JUSTICE DURING THE COVID-19 PANDEMIC - Bagijo, Himawan Estu; Santoso, Hendrawan Dendy (Fakultas Syariah, 2021)
Workers and employers felt the impact of Covid-19 that spread among the labor cluster. One of the problems is wage. The novelty of this research is the discussion of the governmentâ€™s point of view on the differences in interests based on the wages meaning. This paper aims to find out the meaning of wage justice for workers and entrepreneurs during the Covid-19 pandemic through the perspective of Islam. The descriptive qualitative methodology is used to find out the wage justice meaning regarding the reduced wages of the workers that are on the essential category, 51 companies with 3,032 workers at the hotel sector and export-oriented industries such as charcoal briquettes and footwear. The data of companies that do not provide wages and lay off the workers on the critical category show 36 companies with 2,290 workers. Most of them are working on the food industry, beverage industry and the supporting sectors. The duties and roles of the Manpower Office, through labor inspectors, are supervising the implementation of the manpower public policies in the form of laws protecting both workers and employers. The formulation of this new policy aims to minimize the employment problems that may occur during the Covid-19 pandemic.Dampak penyebaran Covid-19 klaster ketenagakerjaan dirasakan bagi pekerja dan pengusaha. Salah satu permasalahannya yaitu upah. Kebaruan penelitian ini adalah pembahasan sudut pandang pemerintah terhadap perbedaan kepentingan yang didasarkan pemaknaan upah. Tujuan penulisan artikel ini untuk dapat mengetahui makna keadilan upah bagi pekerja dan pengusaha saat pandemi Covid-19. Jenis penelitian yang digunakan adalah kualitatif deskriptif. Hasil penelitian menunjukkan bahwa pemaknaan upah yang berkeadilan saat upah pekerja yang dikurangi pada kategori esensial sejumlah 51 perusahaan dengan pekerja 3.032 orang yaitu sektorÂ perhotelan dan industri orientasi ekspor seperti arang briket dan alas kaki. Data perusahaan yang tidak memberikan upah sekaligus merumahkan pekerja pada kategori kritikal sejumlah 36 perusahaan dengan pekerja 2.290 orang yang sebagian besar adalah sektor industri makanan dan minuman serta penunjangnya. Tugas dan peran Dinas Tenaga Kerja melalui pegawai pengawas ketenagakerjaan adalah sebagai pembina dalam pelaksaan kebijakan publik ketenagakerjaan berupa perundangan yang melindungi baik pekerja maupun pengusaha. Perumusan kebijakan baru ini adalah untuk meminimalisasi timbulnya masalah ketenagakerjaan saat pandemi Covid-19.